Comparative analysis of antibiotic resistance genes between fresh pig manure and composted pig manure in winter, China - Shuai Huang; Minghui Xing; Haifeng Wang (PLoS ONE, 2025)
Antibiotic resistance is a critical global public health issue. The gut microbiome acts as a reservoir for numerous antibiotic resistance genes (ARGs), which influence both existing and future microbial populations within a community or ecosystem. However, the differences in ARG expression between fresh and composted feces remain poorly understood. In this study, we collected eight samples from a farm in Kaifeng City, China, comprising both fresh and composted pig manure. Using a high-throughput quantitative PCR array, we analyzed differences in ARG expression between these two types of manure. Our findings revealed significant differences in ARG profiles, as demonstrated by principal coordinate analysis (PCoA). Further analysis identified 39 ARGs (log2FC > 1, p < 0.05) in composted pig manure, with 25 genes downregulated and 14 upregulated. Notably, tetB-01, blaOCH, and blaOXY were the most abundant in composted pig manure compared to fresh manure. Additionally, 16S rRNA species profiling revealed that the composting process significantly altered the microbial community structure, with an increased abundance of Firmicutes and a decreased abundance of Bacteroidetes in composted pig manure. In summary, composting substantially transforms both the microbial community structure and the ARG profile in pig manure, underscoring its potential role in modulating the dynamics of ARGs in agricultural environments.